009. Evaluation of respiratory symptoms in the emergency department - Kalkantzi, Athanasia (J Thorac Dis, 2015)
OBJECTIVE: To evaluate the prevalence of respiratory symptoms and comorbidities, the final diagnosis and the management of patients reviewed in the emergency department of a district hospital of Kavala. METHODS: We have retrospectively reviewed medical records of adult patients presented in the emergency department in January 2013. Most frequent symptoms included cough, dyspnea, chest pain, haemoptysis. Statistical analysis has been performed using SPSS 18. RESULTS: Of the 142 people who visited the emergency department, 73 out of 142 patients (51.4%) were males, 69 out of 142 patients (48.6%) were females of average age 59.6±21.6 years old. The most frequent symptoms are as follows: Most frequent comorbidities included: arterial hypertension (23, 16.2%), congestive heart failure (CHF) (16, 11.3%), chronic obstructive pulmonary disease (COPD) (18, 12.7%), diabetes mellitus (15, 10.6%), coronary artery diseases (CAD) (25, 17.7%), lung cancer (8, 5.6%), bronchial asthma (7, 4.9%), neurologic disorders (5, 3.5%), chronic renal failure (4, 2.8%) others 9.8%. Final diagnosis included: lower tract respiratory infection (85, 59.9%), upper tract respiratory infection (12, 8.5%), COPD exacerbation (12, 8.5%), lung cancer (7, 4.9%), CHF and CAD (9, 6.3%), asthma exacerbation (2, 1.4%), tuberculosis (2, 1.4%), fever of unknown origin (2, 1.4%), pleural effusion (1, 0.7%), pulmonary embolism (1, 0.7%), pneumothorax (1, 0.7%), panic attack (1, 0.7%), musculoskeletal pain (1, 0.7%). Management: drug prescription, no need for admission (83, 58.4%), admission in the Respiratory Medicine Department (44, 31%). Referral to: Cardiology Department (9, 6.3%), Internal Medicine Department (2, 1.4%), General Surgery Department (1, 0.7%), Orthopedic Department (1, 0.7%), ENT Department (1, 0.7%), Psychology Department (1, 0.7%). CONCLUSIONS: Respiratory symptoms need to be evaluated carefully in the emergency department. They are not specific for respiratory disorders, can be also associated with other diseases and require a very detailed diagnostic work-up. Careful evaluation of comorbidities is equally important.